2007
DOI: 10.1111/j.1469-8749.2007.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of hyperbaric oxygen therapy for cerebral palsy: the state of the evidence

Abstract: A systematic review of the evidence was conducted on the benefits and adverse effects of hyperbaric oxygen treatment (HBOT) for cerebral palsy (CP). Studies of any HBOT regimen in patients with CP were included except for case reports and case series. Electronic databases (e.g. MEDLINE, EMBASE), professional society databases, and reference lists were searched to identify studies. Study quality was assessed using predefined criteria relevant to the study design. Two randomized controlled trials and four observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 19 publications
2
28
0
1
Order By: Relevance
“…When motivated parents participate in CAM studies, placebo or participation effects have repeatedly proven to be powerful confounders. 103,140 Additionally, child development is dynamic, and improvement over time is expected, which makes distinguishing the effects of individual treatments, whether they be conventional treatments or CAM treatments, especially problematic in uncontrolled studies. 6 Understanding the power of these confounders will help clinicians and parents avoid therapies that are either potentially harmful or that simply have no benefits over placebo in producing the desired outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When motivated parents participate in CAM studies, placebo or participation effects have repeatedly proven to be powerful confounders. 103,140 Additionally, child development is dynamic, and improvement over time is expected, which makes distinguishing the effects of individual treatments, whether they be conventional treatments or CAM treatments, especially problematic in uncontrolled studies. 6 Understanding the power of these confounders will help clinicians and parents avoid therapies that are either potentially harmful or that simply have no benefits over placebo in producing the desired outcome.…”
Section: Discussionmentioning
confidence: 99%
“…100 -102 Early uncontrolled studies of HBO 2 T demonstrated benefit in children with cerebral palsy, but later controlled studies clearly established no benefit of treatment with HBO 2 T, compared with placebo. 102,103 Hyperbaric oxygen therapy is generally regarded as safe, but there are some common adverse effects, with reversible myopia due to direct oxygen toxicity of the lens and otic barotrauma occurring in up to 20% of individuals. 104 More serious adverse effects can occur, including seizures, hypoglycemia, tympanic membrane rupture, and pulmonary complications.…”
Section: Biologically Based Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of outstanding clinical value is their final observation: patients who regain consciousness move through a series of clinical improvements beginning with appearance of sustained visual pursuit; clinical improvement occurs in parallel with imaging changes supporting reconnections of corticothalamic-cortical associations [37,38]. Other authors have termed the concept of viable but inactive neurons that can be stimulated into recovery as the idling neurons hypothesis [39]. Consideration of this general model of PVS correlates with research findings and resulting hypotheses regarding mechanisms underlying the efficacy of SCS as facilitator of recovery after brain injury [25,30].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperbaric oxygen therapy has been investigated in the treatment of many neurological conditions including stroke (Anderson et al 1991;Nighoghossian & Trouillas 1995;Rusyniak et al 2003;Singhal 2007), traumatic brain injury McDonagh et al 2004;Rockswold et al 2007;Shi et al 2006), cerebral palsy (Collet et al 2001;Hardy et al 2002;McDonagh et al 2007), and multiple sclerosis (Bennett & Heard 2004;Kleijnen & Knipschild 1995).…”
Section: Previous Studies On Hyperbaric Oxygen Therapymentioning
confidence: 99%